Interference-free broadband single- and multicarrier DS-CDMA. - Wei, H.; Yang, L.L.; Hanzo, L.
The choice of the direct sequence spreading code in DS-CDMA predetermines the properties of the system. This contribution demonstrates that the family of codes exhibiting an interference-free window (IFW) outperforms classic spreading codes, provided that the interfering multi-user and multipath components arrive within this IFW, which may be ensured with the aid of quasi-synchronous adaptive timing advance control. It is demonstrated that the IFW duration may be extended with the advent of multicarrier DS-CDMA proportionately to the number of subcarriers. Hence, the resultant MC DS-CDMA system is capable of exhibiting near-single-user performance without employing a multi-user detector. A limitation of the system is that the number of spreading codes exhibiting a certain IFW is limited, although this problem may be mitigated with the aid of novel code design principles
Keywords: direct sequence spreading code; interference-free broadband multicarrier DS-CDMA.; interference-free broadband single-carrier DS-CDMA.; interference-free window quasisynchronous adaptive timing advance control; random code